2021
DOI: 10.7554/elife.70071
|View full text |Cite
|
Sign up to set email alerts
|

Memory recall involves a transient break in excitatory-inhibitory balance

Abstract: The brain has a remarkable capacity to acquire and store memories that can later be selectively recalled. These processes are supported by the hippocampus which is thought to index memory recall by reinstating information stored across distributed neocortical circuits. However, the mechanism that supports this interaction remains unclear. Here, in humans, we show that recall of a visual cue from a paired associate is accompanied by a transient increase in the ratio between glutamate and GABA in visual cortex. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 104 publications
2
19
0
Order By: Relevance
“…Identified CFC- driven transcript changes in inferior blade, while fewer, followed a similar overall pattern – i.e., transcripts involved in glutamatergic synapse biogenesis were upregulated, while GABA receptor transcripts were downregulated, after CFC. This strongly supports the hypothesis that excitatory- inhibitory balance changes in specific brain circuits accompanies, and benefits, long-term memory storage (54)(20, 55, 56). The finding that these changes are constrained to DG, among all subregions profiled, is consistent with the prior finding of sustained transcriptomic changes occurring specifically within DG engram neurons 24 h post-CFC (57), and may reflect unique dynamics of the DG network (or the engram neurons within it), which could plausibly outlast changes after learning in other hippocampal structures (11, 58, 59).…”
Section: Discussionsupporting
confidence: 85%
“…Identified CFC- driven transcript changes in inferior blade, while fewer, followed a similar overall pattern – i.e., transcripts involved in glutamatergic synapse biogenesis were upregulated, while GABA receptor transcripts were downregulated, after CFC. This strongly supports the hypothesis that excitatory- inhibitory balance changes in specific brain circuits accompanies, and benefits, long-term memory storage (54)(20, 55, 56). The finding that these changes are constrained to DG, among all subregions profiled, is consistent with the prior finding of sustained transcriptomic changes occurring specifically within DG engram neurons 24 h post-CFC (57), and may reflect unique dynamics of the DG network (or the engram neurons within it), which could plausibly outlast changes after learning in other hippocampal structures (11, 58, 59).…”
Section: Discussionsupporting
confidence: 85%
“…Among hippocampal neurometabolites, learning to locate the visible platform in the water maze, learning to locate the hidden platform water maze, and cued fear memory were linked to lower levels of GABA. These data are consistent with the disruption of fear memories following pre-and post-training administration of drugs that facilitate GABA neurotransmission (Makkar et al, 2010) and the increase ratio in glutamate to GABA in hippocampus and visual neocortex when human study participants recalled visual cues in a virtual environment in which specific sounds predicted the appearance of particular visual patterns and some patterns led to a monetary award (Koolschijn et al, 2021). As cued fear memory is not hippocampus-dependent (Phillips and Ledoux, 1992), these data suggest that these relationships are not necessarily restricted to the hippocampus.…”
Section: Discussionsupporting
confidence: 75%
“…This manifests clinically as a decline in memory, cognition, and general functioning over time. Recent research has demonstrated that memory recall in the visual neocortex is strongly dependent on hippocampal glutamate excitatory levels and may explain why memory is disrupted in numerous neuropsychiatric disorders [ 135 ].…”
Section: The Glutamate Hypothesis Of Schizophreniamentioning
confidence: 99%